(untitled) (Cadernos de Sociomuseologia, 2015)
The article presents the perspectives and pratices of Museu do Patrimônio Vivo de João Pessoa. For this, analyzes the museological process that operates in the Greater João Pessoa, Paraíba, Brazil. The museum’s mission is community development by proposing actions to safeguard intangible heritage together with young people from the communities involved. The article explores the conceptual innovations that made possible the creation of a museum without walls, located in representative places of cultural activities - such as home cultural masters and agents, work places, parties, celebrations and games - and to be construed as environment dynamic, joint construction, promoting the connection between cultural actors from different communities. Keywords: Museum; museological process; Intangible Cultural Heritage; João Pessoa.